Anteseden Turnover Intention pada Karyawan Rumah Sakit “X” Bandung Barat - Albert Kurniawan Purnomo; Wanti Pebriani (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2020)
Abstract: This study aims to discuss the perceived influence of organizational support on turnover intentions in hospital employees in West Bandung. This research was conducted on 67 respondents of hospital employees using quantitative methods. The data collection tool consists of a questionnaire. The data analysis technique used is descriptive statistical analysis using averages and simple linear regression analysis using the IBM SPSS24 program. The results of this study indicate that the perception of organizational support at Hospital X is categorized quite high and considered a significant influence between the perception of organizational support for turnover intention in Hospital employees. The result view negative relationships between variables. The perceived increase in organizational support will reduce turnover intentions. Keywords: Perceived Organizational Support (POS), Turnover Intention. Abstrak: Penelitian ini bertujuan untuk menguji pengaruh perceived organizational support terhadap turnover intention pada karyawan rumah sakit di Bandung Barat. Penelitian ini dilakukan pada 67 responden karyawan rumah sakit dengan menggunakan metode kuantitatif. Alat pengumpul data berupa kuesioner. Teknik analisis data yang digunakan yaitu teknik analisis statistik desktiptif dengan menggunakan rata-rata dan analisis regresi linier sederhana dengan menggunakan program IBM SPSS24. Hasil penelitian ini menunjukkan bahwa perceived organizational support pada rumah sakit berada dikategori cukup tinggi dan terdapat pengaruh yang signifikan antara perceived organizational support terhadap turnover intention pada karyawan rumah sakit. Dari hasil terlihat, terdapat hubungan yang negatif antara kedua variabel. Peningkatan perceived organizational support akan menurunkan tingkat turnover intention. Kata Kunci : Perceived Organizational Support (POS), Turnover Intention